Adillatu al-Nahw Fi Syarh Kitab al-Kawakib al-Durriyyah 'Ala Mutammamah al-Ajrumiyah wa Atsar Isti'maluha 'Ala Fahm al-Qowaid al-Nahwiyah - Asrina, Asrina; Lubis, Arbonas (Institut Agama Islam Negeri (IAIN) Curup, 2019)
The objectives of this study were to find out the syntax evidence (adillah al-nahwu) in the book Syarh Kitab al-Kawakib al-durriyah ?ala Mutamammimah al-Ajrumiyyah, how to use the evidence of syntax (adillah al-nahwu) in it?s book, and what are the effects of syntax evidence (adillah al-nahwu) in grammatical rules. The purposes of the research are to find out the syntax evidence (adillah al-nahwu) in the book Syarh Kitab al-Kawakib al-durriyah ?ala Mutamammimah al-Ajrumiyyah and to explain the evidence of syntax (adillah al-nahwu) found in it?s book, and to know the effects of the evidence of syntax (adillah al-nahwu) in the grammar rules. This research used library research where the data were collected through document analysis. The results of the research that the most adillah that used Ar-Ru?ainiy were sama? or naql, ijma?, and Hadith. Dalil al-Sama? of the Qur'an used in the book Syarh Kitab al-Kawakib al-Durriyah ?ala Mutamammimah al-Ajrumiyyah were 102 evidences, dalil of Hadith were 12 evidences, dalil of the words of the Arabs were 60 evidences, 1 dalil of ijma? , and 4 dalil of istishab al-hal. The syntax evidence (adillah al-nahwu) in the book Syarh Kitab al-Kawakib al-Durriyah ?ala Mutamammimah al-Ajrumiyyah affect on availability for the understanding of the grammar rules.